HISTOLOGICAL CHANGES OF WHITE RATS DENTAL HARD TISSUES DURING ALIMENTARY OBESITY - Антонишин, І.В.; Марущак, М.І.; Бржиський, А.В. (World of Medicine and Biology, 2015)
In dentin of rats of experimental group dentical tubules took place radially, as in intact animals, however in near to enamel zones of cloak dentin clearness of contours of tubules was lost, structureless areas were visualized, that indicates destruction of dentin. At the same time observed focus, where concentration of tubules increased in sight what can be considered manifestation of compensatory phenomena. Thus in all layer of cloak dentin basic substance prevailed over pinches of collagen fibers. It was found that in case of alimentary obesity in rats occurred the damage of the enamel organic matrix, as evidenced by significant growth relative area of enamel without prism and decrease the relative lengths of enamel plates. Dentin changes were characterized by destruction of dentin tubules, whose number was significantly reduced as in the area of enamel-dentin border, and near the pulp.
Keywords: obesity; micropreparations of rats decalcined teeth; experiment